Self-control in animals and people - Beran, Michael J. (Academic Press, an imprint of Elsevier, 2018)
"Self-control in animals and people takes an interdisciplinary look at what self-control is, how it works, and whether humans are alone as a species in their ability to demonstrate self-control. the book outlines historical and recent empirical approaches to understanding when self-control succeeds and fails, and which species may share with humans the ability to anticipate better future outcomes. It also provides readers with in-depth explorations of whether various species can delay gratification, the ways in which people and animals exhibit other forms of self-control, what influences the capacity and expression of self-control, and much more. In addition to its comprehensive coverage of self-control research, the book also describes self-control assessment tests that can be used with young children, adults, and a wide variety of nonhuman species, with the goal of making fair and clear comparisons among the groups."--Provided by publisher